The relationship of personal characteristics and dispositional greed - Shirko, Svetlana M. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article focuses on the study of greed as a stable personality trait and motivation. The relevance of the study of personal factors in the context of the study of dispositional greed is substantiated. Insatiability, avarice, possessiveness, envy, egoism, materialism, neuroticism, psychoticism are considered as psychological characteristics of greed as a stable motivation. The correlation analysis revealed the nature of the relationship between personal characteristics and dispositional greed of men and women.